Effects from metal ion in tumor endothelial marker 8 and anthrax protective antigen: BioLayer Interferometry experiment and molecular dynamics simulation study. Issue 15 (5th June 2017) - Jia, Zhe; Ackroyd, Christine; Han, Tingting; Agrawal, Vibhor; Liu, Yinling; Christensen, Kenneth; Dominy, Brian
Abstract : One of the anthrax receptors, tumor endothelial marker 8 (TEM8), is reported to be a potential anticancer target due to its over‐expression during tumor angiogenesis. To extend our BioLayer Interferometry study in PA‐TEM8 binding, we present a computational approach to reveal the role of an integral metal ion on receptor structure and binding thermodynamics. We estimated the interaction energy between PA and TEM8 using computer simulation. Consistent with experimental study, computational results indicate the metal ion in TEM8 contributes significantly to the binding affinity, and PA‐TEM8 binding is more favorable in the presence of Mg 2+ than Ca 2+ . Further, computational analysis suggests that the differences in PA‐TEM8 binding affinity are comparable to the closely related integrin proteins. The conformation change, which linked to changes in activity of integrins, was not found in TEM8. In the present of Mg 2+, TEM8 remains in a conformation analogous to an integrin open (high‐affinity) conformation. © 2017 Wiley Periodicals, Inc. Abstract : Tumor endothelial marker 8 (TEM8) is reported to bind to a potential anticancer target, protective antigen (PA), through an integral metal ion. Consistent with BioLayer Interferometry experiments, computer simulations indicate the metal ion contributes significantly to the binding affinity. TEM8‐PA binding is more favorable in the presence of a smaller ion like Mg 2+, rather than a larger ion like Ca 2+ . Moreover, the conformation change, which links to the change in activity of integrins, was not found in TEM8. In the presence of Mg 2+, TEM8 remains in a conformation analogous to an integrin open (high‐affinity) conformation.